A genetic variant within MDM4 3′UTR miRNA binding site is associated with HPV16‐positive tumors and survival of oropharyngeal cancer. Issue 12 (12th September 2019) - Zhang, Yang; Sturgis, Erich M.; Wei, Peng; Liu, Hongliang; Wang, Ziqiao; Ma, Yiding; Liu, Chuan; Gu, Kyle J.; Wei, Qingyi; Li, Guojun
Abstract: As mouse double minute 4 (MDM4) and HPV16 E6 oncoproteins play important roles in inhibition of p53 activity, a functional polymorphism (rs4245739) in the 3′ untranslated regions of MDM4 targeted by microRNA‐191 may alter its expression level or functional efficiency, thus affecting tumor status and survival in human papillomavirus (HPV)‐positive squamous cell carcinoma of oropharynx (SCCOP). A total of 564 incident SCCOP patients with definitive radiotherapy were included for determination of tumor HPV16 status and genotypes of the polymorphism. Univariate and multivariable Cox models were performed to assess the associations between the polymorphism and outcomes. We found that MDM4 rs4245739 had statistically significant associations with tumor HPV‐positivity and survival of SCCOP patients. Patients with AC/CC variant genotypes of MDM4 rs4245739 were approximately 3‐fold more likely to be HPV16‐positive tumors among SCCOP patients compared with common homozygous AA genotype (adjusted odds ratio = 3.2, 95% confidence interval = 1.9‐5.5). Moreover, patients with MDM4 rs4245739 AC/CC variant genotypes had significantly better overall, disease‐specific, and disease‐free survival compared with those with the corresponding common homozygous AA genotype (all log‐rank =  P  < .05); and these genotypes were significantly associated with an approximately three to four times reduced risk of overall death, death owing to disease, and recurrence after multivariable adjustment. Finally, the significant effects of MDM4 rs4245739 polymorphism on survival were found among HPV16‐positive SCCOP patients only after the stratified analyses by tumor HPV status. We concluded that MDM4 rs4245739 polymorphism is significantly associated with tumor HPV status and survival of SCCOP, especially in HPV16‐positive SCCOP patients treated with definitive radiotherapy; nevertheless, prospective larger studies are warranted.